Principles of data mining - Bramer, M. A. [ (Max A.)] , 1948- (Undergraduate topics in computer science, 2013)
This book explains the principal techniques of data mining, for classification, association rule mining and clustering. Each topic is clearly explained and illustrated by detailed examples, with a focus on algorithms rather than mathematical formalism